2011
DOI: 10.1016/j.pain.2011.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte expression of calcitonin gene-related peptide β: Implications for neuropathic and inflammatory pain mechanisms

Abstract: Calcitonin Gene-Related Peptide (CGRP) is a vasodilatory peptide that has been detected at high levels in the skin, blood, and cerebral spinal fluid under a variety of inflammatory and chronic pain conditions, presumably derived from peptidergic C and Aδ innervation. Herein, CGRP immunolabeling (IL) was detected in epidermal keratinocytes at levels that were especially high and widespread in the skin of humans from locations afflicted with postherpetic neuralgia (PHN) and complex region pain syndrome type 1 (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 111 publications
(180 reference statements)
5
126
0
1
Order By: Relevance
“…It is possible that NADA treatment reduced CGRP secretion via the acute desensitization of TRPV1, but this seems unlikely because, similar to other reports, we observed that NADA TRPV1-dependently increases levels of substance P in the circulation. Finally, the neuropeptides in the plasma may have been derived from nonneuronal cells, such as keratinocytes, which have been shown to express CGRPb, or subsets of leukocytes that express substance P (69,72).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that NADA treatment reduced CGRP secretion via the acute desensitization of TRPV1, but this seems unlikely because, similar to other reports, we observed that NADA TRPV1-dependently increases levels of substance P in the circulation. Finally, the neuropeptides in the plasma may have been derived from nonneuronal cells, such as keratinocytes, which have been shown to express CGRPb, or subsets of leukocytes that express substance P (69,72).…”
Section: Discussionmentioning
confidence: 99%
“…24 Both CGRP isoforms, -α and -β, have similar activity, though CGRP-α is the predominant isoform in human skin and colocalizes with substance P. 24 Recent evidence suggests that CGRP-β is produced by epidermal keratinocytes and upregulated in certain cutaneous pain syndromes. 25 Upregulation of substance P and CGRP may be mediated through activation of nonselective cation channels TRPV1 and TRPA1 (transient receptor potentials vanilloid 1 and ankyrin 1); agonists of TRPV1 and TRPA1 have been shown in mice to cause increased blood flow via upregulation of vasodilator neuropeptides such as substance P and CGRP. 26 Certain stimuli (eg, heat, cold, spices) may lead to activation of TRPV1 and TRPA1, with subsequent upregulation of substance P and CGRP and further downstream vasodilation, producing the typical flush of rosacea.…”
Section: -23mentioning
confidence: 99%
“…CGRP conveys pain information from nociceptors to second-order neurons in the spinal cord, and it is also an important mediator of normal inflammatory pain response to injuries [60,61]. CGRP is also involved in the development of hyperalgesia in inflammation-or nerveinjury-induced chronic pain [62]. Studies in vivo suggest that the conditional overexpression of BMP4 in mouse skin keratinocytes reduces the number of non-peptidergic neurons in sensory ganglia and the density of target innervation, but the nerve endings from CGRP peptidergic neurons were markedly increased [63].This phenotype is consistent with the aforementioned effect of BMP signaling on CGRP expression in vitro [45].…”
Section: Activin and Bmp Retrograde Signals Modulate The Expression Omentioning
confidence: 99%